ANALYSIS OF EFFECT OF YEAST MASS ADDITION AND FERMENTATION TIME TO THE VOLTAGE OF DURIAN (DURIO ZIBETHINUS) HUSK WASTE PASTE - Khairiah Khairiah; Rita Destini (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2017)
Study on the fermentation process of durian (Durio zibethinus) husk waste has been conducted. The fermentation process is done by varying the yeast mass used in the synthesis process and the preparation of the paste. There were also several tests on the duration of the fermentation process to observe the difference of the resulting voltage. In addition, observations were made to measure changes in pH. The pH or degree of acidity is used to express the degree of acidity or base possessed by a substance, solution, or an object. The principle of this study involves only the transport of electrons between two electrodes separated by a conductive medium (electrolyte) that provides electrostatic motion in the form of electrical and current potentials. In the electrolyte electrode, the electrons flowing are carried by the ions and then electrolyzed. The results show that the longer storage time tends to increase the electrical conductivity. This can happen because the acidity of the solution is increasing. In a solution, if the concentration of H+ ions increases, the OH– ion decreases, meaning that the H+ ion moves easily in the solution, so the solution becomes acidic and the electrical conductivity increases. The results showed that the conductivity tends to increase with the length of storage. This happens because the acidity of the solution is increasing. The electrical conductivity shows the ability of the liquid to conduct electricity that is related to the movement of ions in the solution, ions that can move easily have large electrical conductivity.Keywords : Degree of acidity, fermentation, fermentation time, voltage, and yeast mass.